PEMIKIRAN HAJI ABDUL MALIK KARIM AMRULLAH (HAMKA) TENTANG PARTISIPASI POLITIK PEREMPUAN DI INDONESIA TAHUN (1949 – 1963) - Sarah Larasati Mantovani; M. Abdul Fattah Santoso (Profetika: Jurnal Studi Islam, 2015)
Since Mary Wollstonecraft demanded equal rights for women in all fields and denounced all forms of discrimination in her book A Vindication of the Rights of Women in 1792, feminist movements began to emerge and demand the same thing, including the right to participate in politics. Indonesia, which was still called the archipelago, then had given right to women to participate in politics. The motivation of political participation of women in Indonesia was different from that of the Westerners. The motivation of the former was based on a religious spirit, not the spirit of feminism as stated by Hamka in his book Tjemburu (Ghirah). Based on this, this research focuses on Hamka’s thought on Indonesian women political participation. The purpose of this study is to explore and analyze Hamka's thoughts, and construct them, and then associate them with the current Indonesian women political participation. This research is qualitative, based on library research, and done by reviewing, tracking, and analyzing data from the books and newspaper archives. This study uses historical and philosophical. The research data are derived from primary and secondary data sources. The primary data ones are divided into two: first, the primary data sources from Hamka's books that tell about women and women's political participation in general, and, second, the primary data sources from Hamka's books that specifically discuss about Indonesian women's political participation. Analysis of data uses deductive and reflective methods. Based on the results of this research, we can conclude that Hamka had underlined his political thought construction by making the divine revelation as the supreme law. Hamka strengthened the construction of his thought on women's political participation with the element of unity of I'tiqad. This I'tiqad unity was not only in women but also in men, so that they could work together to build a religious Muslim community. Hamka himself basically allowed women (especially a muslim woman) to participate in politics as long as they had religious understanding, knowledge, and high Islamic morale, did not forget their main tasks as wives and mothers, were critical, and dare. Then it could be found as well, the two types of Indonesian women's political participation Hamka's thought, they were based on motivation and activities.